A bioactive implant combining isoniazid with nanohydroxyapatite/polyamide 66 for the treatment of osteoarticular tuberculosis. (15th November 2021) - Xie, Tianhang; Song, Yueming; Peng, Haitao; Dai, Zhongqiu; Kang, Yi; Xiu, Peng; Wang, Linnan; Li, Hong; Yang, Xi
Graphical abstract: Highlights: The isoniazid-loaded nanohydroxyapatite/polyamide 66 (n-HP@ICG) scaffold can effectively and safely release the drug. n-HP@ICG strongly inhibited the activity of Mycobacterium tuberculosis. Satisfactory osteoconduction and osseointegration capacities remained in n-HP@ICG. Abstract: Maintaining an effective drug concentration in the nidus during the early stage is essential for the surgical treatment of osteoarticular tuberculosis (TB) and the prevention of internal infection. In this study, an implantable composite scaffold, denoted as n-HP@ICG, was synthesized by attaching isoniazid (INH) to chitosan followed by crosslinking via glutaraldehyde to porous nanohydroxyapatite/polyamide 66 (n-HA/PA66). Drug release and biocompatibility experiments showed that INH could be effectively released from the composite scaffold for approximately 15 days in vitro and 28 days in vivo with no obvious cytotoxicity or harm to liver or kidney function. The anti-TB test indicated that n-HP@ICG had satisfactory anti-TB effects, including the inhibition of Mycobacterium tuberculosis activity, proliferation and adhesion. The rabbit femoral condyle defect repair experiment showed that the composite scaffold had satisfactory osteoconduction and osseointegration. These results demonstrate that the n-HP@ICG composite scaffold can simultaneously provide relatively long-term drug release, biosafety, and anti-TB and bone regeneration activity and is thus promising for treating osteoarticular TB.